Study Literature of Development Model of Mathematics Curriculum in Queensland - Zahid Abdush Shomad; Iwan Junaedi; Mulyono Mulyono (Universitas Tidar, 2021)
Australia grants individual states autonomy to develop school mathematics curricula. This article aims to find out a model for developing a school mathematics curriculum in Queensland. The method used in this research is Systematic Literature Review (SLR). This SLR method can be used to identify, review, evaluate, and interpret studies related to the topics discussed in this study, with specific relevant research questions. The SLR method in this research is carried out by systematically reviewing and identifying journals, which follow the steps or protocols that have been set in each process. The documents studied and researched include journals and professional scientific papers and Queensland mathematics curriculum documents for grades 11 and 12, namely the Queensland Curriculum & Assessment Authority (QCAA). Based on the results of the literature review, it was found that in Queensland, the mathematics curriculum in grades 11 and 12 is divided into three types, namely Mathematics A curriculum, Mathematics B curriculum, and Mathematics C curriculum. Each type of curriculum is developed according to the conditions and skills required by students.